A self-administered test of taste function using "Taste Strips" - Wolf, Axel; Varga, Laszlo; Wittibschlager, Lisa; Renner, Bertold; Mueller, Christian A. (International Forum of Allergy and Rhinology, 2016)
Assessment of gustatory function with impregnated taste strips is an established and validated method. In clinical routine, application of the tests is often limited due to lack of time or costs associated with administering the test. The aim of the study was to develop a procedure suitable for self-administration of the "Taste Strips" test.The investigated participants (n = 65; 22 males, 43 females; mean age 36.7 ± 19.2 years; range, 20 to 83 years) were tested twice in a randomized crossover procedure. On 1 occasion, an examiner administered the established and validated "Taste Strips" test. On another occasion, test subjects administered the taste strips themselves. Results of both test methods were compared.The mean score (± standard deviation [SD]) of the assisted taste test (11.6 ± 2.6) was significantly lower compared to the mean self-administered taste test that yielded 12.3 ± 2.6 points (Wilcoxon test: z = 2.836; p < 0.01). Comparison of mean values showed minimal difference of the tested procedures of 0.7 ± 1.9 points with a significant positive correlation of test results (r65 = 0.734; p < 0.01).Although a small difference between test results was observed, the new test procedure seems to be an adequate screening tool for assessment of taste function with less personnel effort, leading to improved management of patients with chemosensory disorders.
EVALuna2:8525